A study of beliefs mathematical with mathematical reasoning for grade seven students - Saensena, Piyapat; Thipchart , Yuthapong (Journal for Developing the Social and Community, 2024)
The purposes of this research were (1) to study the mathematical beliefs for grade seven students, (2) to study the mathematical reasoning level for grade seven students and (3) to study the relationship between beliefs in mathematics. Mathematical reasoning and mathematical reasoning for grade seven students. The target group used in this research were Mathayomsuksa 1 students at Roi-Et Wittayalai School, Muang Roi-Et District. Roi Et Province, 2nd semester, academic year 2022, 298 students obtained by stratified random stratification. (Proportional Stratified Random Sampling) with classroom type as the classification class. The research tools were mathematics belief test. Mathematics reasoning test and a semi-structured interview about mathematical belief level and mathematical reasoning. Statistics used in data analysis were frequency, percentage, mean, standard deviation. Pearson’s correlation coefficient A case study method was also used to present the data. Descriptive Analysis The results of the research revealed that (1) Mathematics belief level of Mathayomsuksa 1 students was quite high. (2) The level of mathematical reasoning of Mathayomsuksa 1 students was mostly level 3, which is the level of reasoning that is expressed in informal numbers. with rational thinking strategies representing 43.96 percent. (3) There is a strong relationship between mathematical belief and mathematical reasoning. has a correlation coefficient of .733 And from the interviews, it was found that the students’ beliefs in mathematics were high and quite high. Able to solve problems and reason able to use correct thinking and calculation skills students with moderate mathematical beliefs Can explain concepts and solutions. but cannot solve complex problems Students with relatively low mathematical beliefs Irrelevant reasons were given. Inability to explain concepts and find answers and students with low mathematical beliefs. Inability to explain concepts and find answers.